Unusual Nonpolynomial Van der Pol Oscillator Equations With Exact Harmonic and Isochronous Solutions - ADJAÏ, K. K. Damien; NONTI, Marcellin; Akande, Jean; MONSIA, MARC DELPHIN (My University, 2022)
We do not know Van der Pol-type equations with nonlinear restoring force having explicitly an exact periodic solution. We present, for the first time, nonpolynomial Van der Pol oscillator equations that do not satisfy the classical existence theorems. We exhibit their exact harmonic and isochronous solutions and prove the existence of limit cycles by using averaging theory. We also present first integrals and exact solutions of polynomial Van der Pol-Duffing equations to show that they do not have any limit cycle. Additionally, we prove that the damped Duffing-type equations are equivalent to the conservative Duffing equations exhibiting nonoscillatory solutions.
Keywords: Van der Pol-Duffing equation; nonpolynomial Van der Pol-type oscillator; damped Duffing; equation; first integrals; exact harmonic and limit cycle solutions; existence theorem.